2017
DOI: 10.1186/s12871-017-0418-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Supreme™ and ProSeal™ laryngeal mask airways in infants: a prospective randomised clinical study

Abstract: BackgroundThe Supreme™ and ProSeal™ laryngeal mask airways (LMAs) are widely used in paediatric anaesthesia; however, LMA use in infants is limited because many anaesthesiologists prefer to use tracheal intubation in infants.In this study, we compared the Supreme and ProSeal LMAs in infants by measuring their performance characteristics, including insertion features, ventilation parameters, induced changes in haemodynamics and rates of postoperative complications.MethodsInfants of ASA physical status I schedul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…In this study, the I-gel and ProSeal LMA were compared in infants. Due to the proven safety of the ProSeal LMA in infants and the results of our previous study that showed that ProSeal LMA is safer than Supreme LMA in infants, we preferred to compare I-gel with ProSeal LMA in this study ( 4 , 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the I-gel and ProSeal LMA were compared in infants. Due to the proven safety of the ProSeal LMA in infants and the results of our previous study that showed that ProSeal LMA is safer than Supreme LMA in infants, we preferred to compare I-gel with ProSeal LMA in this study ( 4 , 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…The Laryngeal Mask Airway ProSeal has undergone numerous studies since its inception and shown to provide superior oropharyngeal leak pressures compared to other SGAs . The i‐gel may have a slight advantage in practicality since institutions may be less inclined to use reusable devices, such as the ProSeal.…”
Section: The “Best” Of What We Havementioning
confidence: 99%
“…In contrast, an example of a good research question would be: among children younger than 1 year of age undergoing elective minor procedures, to what extent the insertion times are different, comparing the Supreme™ laryngeal mask airway (LMA) to Proseal™ LMA, when placed after reaching a BIS index <60? [10] In this example, the core ingredients of the research question can be easily identified as: children <1 year of age undergoing minor elective procedures, Supreme™ LMA, Proseal™ LMA and insertion times at anaesthetic induction when reaching a BIS index <60. These components are usually gathered in the literature under the acronym of PICOT (population, intervention, comparator, outcome and time frame, respectively).…”
Section: Optimisation Of Time and Resourcesmentioning
confidence: 99%
“…[14] In one clinical trial, authors stated: “we compared the Supreme™ and ProSeal™ LMAs in infants by measuring their performance characteristics, including insertion features, ventilation parameters, induced changes in haemodynamics, and rates of postoperative complications”. [10] Here, the research question has been centered on the measurements (insertion characteristics, haemodynamic variables, LMA insertion characteristics, ventilation parameters) rather than the clinical problem that needs to be addressed (is Supreme™ LMA easier to insert than ProSeal™ LMA? ).…”
Section: Picot Frameworkmentioning
confidence: 99%
See 1 more Smart Citation